Wprowadzenie dziecka w świat literatury dziecięcej przez rodziców = Introduction of child into the world of children`s literature by parents - Walak, Bogumiła (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The aim of this article was to outline the correlation between the children`s literature and their development (parti cularly in the preschool period). Moreover in the field of interest was to define the role of literature in stimulation of the child`s development in parent`s opinion.
Keywords: wpływ literatury dziecięcej; ilustracja w książkach dla dzieci; literatura dziecięca; czytanie książek dla dzieci przez rodziców; influence of children`s literature; illustration in books for children; children`s literature; reading books to children by parents; parent as connection among child and literature